2005
DOI: 10.1210/jc.2004-1895
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Is Involved in Osteoprotegerin-Induced Chemotaxis in Human Peripheral Blood Monocytes

Abstract: Chronic inflammation is characterized by tissue infiltration with monocytes/macrophages, which possess broad proinflammatory, destructive, and remodeling capacities. Elevated levels of osteoprotegerin, an important regulator of differentiation and activation of osteoclasts that also affects different cells of the immune system, were found in the serum of patients with chronic inflammatory diseases. The study of whether osteoprotegerin affects monocyte locomotion in vitro and the possible mechanisms and pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 49 publications
2
52
0
2
Order By: Relevance
“…Another proposed binding partner for OPG is syndecan-1, and data suggest that OPG can mediate the migration of monocytes via interaction with syndecan-1. 28 Interestingly, the expression of syndecan-1 has been shown to be increased in a rabbit aortic neointimal model; 29 however, we failed to detect expression of syndecan-1 within the pulmonary artery (control or lesions) despite a detectable level of syndecan-1 mRNA in PA-SMCs in culture (A. Lawrie and M. Southwood, unpublished data). The effect of TRAIL on vascular homeostasis is a debated topic with conflicting reports on endothelial cell apoptosis (reviewed by Zauli and Secchiero 30 ) and data suggesting that TRAIL may be a survival, mitotic, and migratory factor for SMCs.…”
Section: Discussionmentioning
confidence: 83%
“…Another proposed binding partner for OPG is syndecan-1, and data suggest that OPG can mediate the migration of monocytes via interaction with syndecan-1. 28 Interestingly, the expression of syndecan-1 has been shown to be increased in a rabbit aortic neointimal model; 29 however, we failed to detect expression of syndecan-1 within the pulmonary artery (control or lesions) despite a detectable level of syndecan-1 mRNA in PA-SMCs in culture (A. Lawrie and M. Southwood, unpublished data). The effect of TRAIL on vascular homeostasis is a debated topic with conflicting reports on endothelial cell apoptosis (reviewed by Zauli and Secchiero 30 ) and data suggesting that TRAIL may be a survival, mitotic, and migratory factor for SMCs.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, OPG induces osteopontin expression via syndecan-1 and activates phosphoinositol 3-kinase/Akt in human periodontal ligament cells (Yongchaitrakul et al 2009). PGs are also involved in OPG-induced chemotaxis of monocytes (Mosheimer et al 2005). Indeed, OPG can interact with syndecan-1 expressed by monocytes (potential osteoclast precursors) and can stimulate the cell migration.…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 99%
“…It has been shown that OPG, through its heparin binding domain interacts with some proteoglycans such as syndecan-1 and that OPG binding to cells expressing high levels of membranous syndecan-1 is internalized, then degraded. 51,52 Similarly, with RANKL expressing cells, the binding of OPG to membranous RANKL is also internalized, yet through another process, the clathrin coat formation pathway, which occurs before proteasomal and lysosomal degradation (Fig. 3).…”
Section: The Opg-rankl Molecular Complexmentioning
confidence: 99%